2006
DOI: 10.1007/s10633-006-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function in Rabbits Does Not Improve 4–5 Months after Terminating Treatment with Vigabatrin

Abstract: Kjellström 2Keywords: Vigabatrin, electroretinogram, immunohistochemistry, drug toxicity. AbstractPurpose: We have previously reported changes in retinal function and histopathology in rabbits treated with vigabatrin. The purpose of the present study was to evaluate retinal function and histopathology of retina in rabbits 4-5 months after terminating vigabatrin medication. Methods: Five rabbits were treated with a daily per oral dose of vigabatrin during 12-13 months. After terminating treatment an observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In the present study, OPs were decreased in both high-dose and low-dose rabbits, reflecting disturbances in inner retinal function, in accordance with several clinical studies revealing OP alterations [11,13,18,19,23,[25][26][27][28]. b-wave amplitudes derived from the isolated cone responses both in rabbits [37,38] and humans [16,49], a well-known phenomenon in VGB treatment [11, 13, 16, 18-20, 22-25, 49],which also has been described in rats [39]. One drawback of the present study is that these results were not repeated.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, OPs were decreased in both high-dose and low-dose rabbits, reflecting disturbances in inner retinal function, in accordance with several clinical studies revealing OP alterations [11,13,18,19,23,[25][26][27][28]. b-wave amplitudes derived from the isolated cone responses both in rabbits [37,38] and humans [16,49], a well-known phenomenon in VGB treatment [11, 13, 16, 18-20, 22-25, 49],which also has been described in rats [39]. One drawback of the present study is that these results were not repeated.…”
Section: Discussionsupporting
confidence: 91%
“…In other studies [9,10,14,15,17,23,35,36], however, neither maximal daily dose nor cumulative dose or length of medication have been correlated to visual field defects or ff-ERG alterations. In prior pilot studies [37,38], we have shown ff-ERG alterations and, occasionally, glial reactions of the retina [37] in rabbits treated with vigabatrin. Similar results are shown by Duboc et al [39], revealing ff-ERG alterations and morphological changes in Müller cells in rats.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Electroretinograms were obtained in rabbits at 8 weeks with a full-field dome method similar to clinical electroretinography (ERG) 19 methods specified by the International Society for Clinical Electrophysiology of Vision (ISCEV) standard. 20 The eyes were dilated with 0.5% tropicamide and dark-adapted for at least 30 min.…”
Section: Electroretinographymentioning
confidence: 99%